Efficiency parameters of endurance athletes while jumping - Boullosa, D.; Tuimil, J. L. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
There is controversy about the rate of force development (RFD) when examining explosive force in dynamic conditions. Its relevance in complex dynamic exercises could be masked by some different factors as its influence in isometric conditions has been extensively demonstrated (Aagaard et al., 2002). Thus, our purpouse was to evaluate kinetics while jumping (CMJ) in a cohort of well trained endurance athletes as they have some homogeneous anthropometric and neuromuscular characteristics that could facilitate the study of selected parameters. Methods 14 male endurance athletes (8 middle-distance runners and 6 triathletes) performed in a force plate (500 Hz) two attempts of CMJ after a warm-up. The depth of countermovement was freely choosen by participants.The best jump was selected for further analysis. The kinetic parameters selected were: peak power (PP), mean power (MP), peak RFD (pRFD), and vertical stiffness (Kvert). Results Significant correlations were found between: pRFD and PP (r = 0,544; p=0,044); pRFD and Kvert (0,693; p=0,006); Kvert and MP (r = 0,808; p=0,000); and Kvert with PP (r = 0,756; p=0,002). Discussion Correlations between Kvert and power measurements suggest an elastic energy transfer between eccentric and concentric actions (Bosco et al., 1982). The novel correlations between RFD and PP suggest an indirect influence of RFD in CMJ performance as PP is highly related to CMJ height. The relationship exhibited between Kvert and RFD, as both are very close in time during force recording, could suggest a reflex origin of this RFD based on previous assumptions (McBride et al., 2008). References Aagaard P, Simonsen EB, Andersen JL, Magnusson P, Dyhre-Poulsen P (2002). J Appl Physiol 93: 1318-26. Bosco C, Tihanyi J, Komi PV, Fekete G, Apor P (1982). Acta Physiol Scand 116(4): 343-9. McBride JM, McCaulley GO, Cormie P (2008). J Strength Cond Res 22(3): 750-7.